1999
DOI: 10.1044/jslhr.4202.497
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Language Achievement in Children With Cochlear Implants and Children Using Hearing Aids

Abstract: English language achievement of 29 prelingually deaf children with 3 or more years of cochlear implant (CI) experience was compared to the achievement levels of prelingually deaf children who did not have such CI experience. Language achievement was measured by the Rhode Island Test of Language Structure (RITLS), a measure of signed and spoken sentence comprehension, and the Index of Productive Syntax (IPSyn), a measure of expressive (signed and spoken) English grammar. When the CI users were compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
122
3
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(139 citation statements)
references
References 17 publications
6
122
3
8
Order By: Relevance
“…In concert, research shows that the speech production skills of deaf children also improve after implantation (Allen, Nikolopoulos, & O'Donoghue, 1998;Brown & McDowall, 1999;Ertmer & Mellon 2001). Finally, several studies have shown that spoken language development is also benefited by experience with a cochlear implant (Blamey, et al, 2001;Bollard, Chute, Popp, & Parisier, 1999;Connor, Hieber, Arts, & Zwolan, 2000;Miyamoto, Kirk, Svirsky, & Sehgal, 1999;Moeller, 2000;Tomblin, Spencer, Flock, Tyler, & Gantz, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In concert, research shows that the speech production skills of deaf children also improve after implantation (Allen, Nikolopoulos, & O'Donoghue, 1998;Brown & McDowall, 1999;Ertmer & Mellon 2001). Finally, several studies have shown that spoken language development is also benefited by experience with a cochlear implant (Blamey, et al, 2001;Bollard, Chute, Popp, & Parisier, 1999;Connor, Hieber, Arts, & Zwolan, 2000;Miyamoto, Kirk, Svirsky, & Sehgal, 1999;Moeller, 2000;Tomblin, Spencer, Flock, Tyler, & Gantz, 1999).…”
mentioning
confidence: 99%
“…In concert, research shows that the speech production skills of deaf children also improve after implantation (Allen, Nikolopoulos, & O'Donoghue, 1998;Brown & McDowall, 1999;Ertmer & Mellon 2001). Finally, several studies have shown that spoken language development is also benefited by experience with a cochlear implant (Blamey, et al, 2001;Bollard, Chute, Popp, & Parisier, 1999;Connor, Hieber, Arts, & Zwolan, 2000;Miyamoto, Kirk, Svirsky, & Sehgal, 1999;Moeller, 2000;Tomblin, Spencer, Flock, Tyler, & Gantz, 1999).When parents are faced with the "cochlear implant decision" for their children, a driving factor in their decision is their "frustration with the child's communication skills" (Kluwin & Stewart, 2000). Improved speech perception and production skills lay the foundation for closing this communication gap; thus it is speech perception and production that are typically hailed as principal benefits of the device.…”
mentioning
confidence: 99%
“…In present study 7.44 children were having cochlear implant while in study conducted by Hintermair et al 7 9.1% children had cochlear implant. 92.56% children were using hearing aid in present study.…”
Section: Discussionmentioning
confidence: 73%
“…Of these children, only 43% demonstrated average language skills for their chronological age, leaving 57% with language delays. Others have reported that children with cochlear implants frequently present with delays in grammatical morphology, regardless of age of implantation (Nikolopoulos, Dyar, Archbold, & O'Donoghue, 2004;Rudmin, 1983;Tomblin, Spencer, Flock, Tyler, & Gantz, 1999). Such delays often persist longer than deficits in other language domains.…”
Section: Discussionmentioning
confidence: 99%